Effect Of Air Velocity On The Quality Of Kiln-Dried Rubberwood (Hevea Brasiliensis) - Ayeru, Singaram (2007)

(untitled)
The objective of this study is to address the effect of air velocity manipulation on drying quality of the rubberwood (Hevea brasiliensis) timber. The study involved three researches. First the industrial assessment of the commercially kiln dried rubberwood, secondly the experimental research to look into the drying behaviour of rubberwood with regard to the air velocity and finally the third research to investigate further the drying behaviour observed in the second research. The industrial study shows that only a quarter of the timber pieces examined are free from any drying defects. Warping was the major defects observed, where spring was highest, followed by bowing and twist defects. Other defects such as end checks and surface checks were also noticed. Although this assessment was not part of the scientific study, the data and the information collected become useful for the next laboratory work. The experimental drying tests performed on the rubberwood produces nonlinear exponential relationship between moisture content (Y) and the drying time (X). Timber subject to 1.52 m/s low air velocity produces Y = 112.87 e -0.0141X (R2 = 0.9395) relationship, while the 3.56 m/s high velocity schedule produces Y = 102.49e -.0.0412X (R2 = 0.9542) relationship and the variable velocity of 3.56 & 1.52 m/s shows Y = 97.10e -0.0145X (R2 = 0.9506). The drying time calculated using these relationships shows that manipulation of air velocity could not improve the drying time of the 3 cm thick timber. The drying time was found to be same irrespective whether it was dried using the 1.52 m/s low air velocity or at higher velocity of 3.56 m/s or varied from 3.56 m/s to 1.52 m/s. Application of higher air velocity during the initial drying period was beneficial. However, the moisture extraction rates become relatively slower at the latter stage and this off-set the time saved during the early period. It was also found that the slower drying rate during the latter drying stage particularly at higher velocity, is mainly due to the moisture being held deep in the wood. The analysis of the moisture content difference between the core and the shell shows that the high velocity drying schedule result in the steepest gradient compared to the other schedules. The observation of the ultra-structure of rubberwood samples by using the Scanning Electron Microscope indicates that the anatomical features particularly the pit aspiration could not account for slowing down the drying rate at the latter stage. Based on the above observations, it is believed that if the temperature is increased higher than what is required by the standard schedule especially at the latter stage of drying, the rate of moisture diffusion from the core can be expedited. In these drying trials, it was observed that rubberwood can be dried without much drying defects by using the standard drying schedule. The quality of the timber that had being subjected to higher air velocity was also not adversely affected. However, the moisture gradient and the drying residual stress increase significantly when higher velocity was used. Analysis of the final moisture content shows “good” relative dispersion among the samples dried at low air velocity schedule compare to the samples from the high velocity and variable velocity schedule. In term of energy saving, the result shows that, when the air velocity is reduced from 3.56 m/s to 1.52 m/s, the corresponding electricity saving is 26 percent. When high velocity schedule is replaced by variable velocity schedule, electrical saving of 16 percent was recorded.